Simvastatin, Sildenafil and Their Combination in Monocrotaline Induced Pulmonary Arterial Hypertension - Lee, Dong Seok (The Korean Society of Cardiology, 2010)
BACKGROUND AND OBJECTIVES: Pulmonary arterial hypertension (PAH) is a life threatening disease characterized by progressive pulmonary arterial occlusion which may ultimately result in death. Currently, the available treatments are diverse, but no therapy alone can reverse the disease process although they may have some clinical benefits. This study was designed to investigate single and combination therapy of simvastatin and sildenafil, which have different mechanisms of action, in monocrotaline (MCT)-induced PAH. METERIALS AND METHODS: Rats were randomized to receive saline (control, n=8) or MCT treatment (n=32). MCT treated rats were randomized to vehicle, simvastatin (2 mg/kg/day), sildenafil (25 mg/kg/day) and a combination simvastatin and sildenafil (n=8, respectively). Three weeks later, hemodynamic study and histologic changes of pulmonary arterioles were measured. Proliferating cell nuclear antigen (PCNA) as well as Western blot for endothelial nitric oxide synthase (eNOS) were performed. RESULTS: Systolic right ventricular pressure was significantly decreased in monotherapy groups (simvastatin and sildenafil) and the combination group compared to MCT group (p<0.05). Right ventricular hypertrophy and medial wall thickness of pulmonary arterioles were significantly attenuated with sole and combination therapy (p<0.05). However, combination therapy did not confer additive benefits over monotherapy. Altered PCNA or eNOS in lung tissue was normalized by either monotherapy or combination therapy. CONCLUSION: The results suggest that either simvastatin or sildenafil has the therapeutic potential in MCT-induced PAH, although combination therapy of these two drugs has failed to show greater benefits in the study.